Application of Tahani Fuzzy Logic in Participant Selection for ONMIPA PT: A Case Study at Institut Teknologi Del - Asido Saragih; Jaya Santoso; Ana Muliyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study investigates the preparation of students for the National Olympiad of Mathematics and Natural Sciences for Higher Education (ONMIPA PT), focusing on the selection process at Institut Teknologi Del (IT Del). The research applies the Tahani fuzzy logic method to select students who demonstrate potential across various mathematical disciplines such as Linear Algebra, Abstract Algebra, Real Analysis, Complex Analysis, and Combinatorics. By using fuzzy logic, students' performances are categorized into three levels: less, adequate, and good. The goal is to ensure a well-rounded selection of participants who can excel in all tested areas, rather than choosing those with the highest scores in individual topics. The results demonstrate that fuzzy logic improves decision-making in selecting participants for the competition. Additionally, the study highlights the broader implications of ONMIPA PT in enhancing educational quality and fostering scientific excellence. This research contributes to the development of selection methods for academic competitions, offering insights into the application of fuzzy logic in multi-stage decision-making processes.